The Effectiveness of Arabic Language Learning in Preventing Bullying Behavior in Students of Luqman AL-Hakim Mataram Integral Elementary School - Suryanti, Beti; Mukhlishin, Mukhlishin; Nurjannah, Nurjannah (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
. Bullying behavior in the elementary school environment is a social problem that has a serious impact on the psychological and social development of students. This study aims to analyze the effectiveness of Arabic language learning as a preventive instrument against bullying behavior through a value-based character education approach. The research uses a qualitative approach with a case study design at SD Integral Luqman Al-Hakim Mataram. Data was collected through observations, in-depth interviews, and documentation of Arabic teachers, homeroom teachers, students, and school management. The results of the study show that learning Arabic that is integrated with the values of manners, empathy, and politeness contributes significantly to shaping students' social attitudes, strengthening a conducive classroom climate, and suppressing the tendency to develop bullying behavior. The process of internalizing values that takes place in a sustainable manner through pedagogical interaction and teacher examples has proven to be more effective than the regulatory approach alone in preventing bullying. This research provides a conceptual contribution in the form of a model of the relationship between value-based Arabic language learning, social attitude change, classroom climate strengthening, and bullying prevention, as well as expanding the perspective of Arabic language learning from linguistic functions to social-preventive functions in Islamic education.